Hardware development of 3 phase unity power factor ac -ac converter - Muhammad Fadzil Jamian. (2013)
Nowadays commercial buildings have lift systems which require variations of frequency. In this case, AC-AC converters are used to support the change of frequency level. The unity power factor can help to reduce the line losses.